Inovasi Choux Au Craquelin dengan Pemanfaatan Tepung Ubi Jalar Ungu (Ipomoea batatas L.Poir) - Kamilatul Hasanah Nur Rahmania Subagyo; Ita Fatkhur; Lilis Sulandari; Nugrahani Astuti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Choux au Craquelin is a variation of choux pastry characterized by a crispy top layer (craquelin) after baking. This product innovation is increasingly in demand due to its unique appearance and texture. This study was conducted with the aim of developing choux au craquelin as a healthier cake product by substituting some wheat flour with purple sweet potato flour. Purple sweet potato flour was chosen because it contains antioxidants, especially anthocyanins, and high dietary fiber, so it is expected to increase the nutritional value of the product without reducing consumer acceptance. The objectives of this study include: (1) Identifying the sensory quality of choux au craquelin based on variations in the proportion of wheat flour and purple sweet potato flour; and (2) Determining the best formula with a combination of the two types of flour. The independent variable in this study is the proportion of purple sweet potato flour to wheat flour, namely 40%:60%, 50%:50%, and 60%:40%. The dependent variable is sensory quality which includes shape, color, texture, aroma, and taste. The control variables included the type of raw materials, equipment, and processing techniques used, so that the manufacturing process was carried out consistently in each treatment. The results showed that the use of purple sweet potato flour significantly affected the sensory quality of the product, especially in terms of color, aroma, texture, and taste. The color of the craquelin became more intensely purplish as the percentage of purple sweet potato flour increased, while the texture tended to be denser but still maintained its characteristic brittleness. In addition, the aroma had a distinctive sweet potato characteristic that was quite liked by the panelists. Further analysis showed an interaction effect between the proportions of wheat flour and purple sweet potato flour on the overall sensory quality.